Military and Crime: A Systematic Review of the Literature. Issue 2 (1st February 2020) - Baktir, Yusuf; Mustafa Icer, Mehmet; Craig, Jessica
ABSTRACT: This study systematically analyzed the literature on the effects of military participation on later criminal behavior. When all studies were analyzed as a whole, the findings did not indicate a clear effect. However, a focus upon specific offense types revealed that the military experience decreased non-violent crime but increased violent crime. Active military personnel tended to be less likely to commit crime. Some evidence demonstrated that male and non-white veterans committed more crime than their civilian counterparts, but future research is needed to replicate these subgroup differences. Theoretical implications and future research directions are also discussed.